Pengaruh perbedaan lama waktu pemberian Spirulina platensis dalam ransum terhadap profil darah merah ayam Broiler - Fuadhy Wahyu Fahmi; Endang Widiastuti; Sugiharto Sugiharto (Faculty of Animal Science, Universitas Brawijaya, 2017)
The study was conducted to evaluate the effect of duration feeding of Spirulina platensis as a prebiotic in ration on the red blood cells of broiler chickens. The material used in this study was 240 day old chick (DOC) with average of initial weight 42.015 ± 0.219 g. The experiment was designed based on Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treated treatments were T0 (Feed Basal + 0.04% Zinc Bacitracin), T1 (Basal diet + 1% Spirulina platensis for 7 days administration), T2 (Basal diet + 1% Spirulina platensis for 21 days of administration) and T3 (Feed Basal + 1% Spirulina platensis for 35 days of administration). Measured variables include total erythrocytes, hemoglobin, percentage of hematocrit, and erythrocyte index values (MCV, MCH, MCHC). Data were analyzed by variance test (F test) and if there was a significant difference then continued with Duncan’s multiple range test. The results showed that there was significant differences (P <0.05) between treatments on total erythrocytes, and no significant differences (P> 0.05) between treatments on hemoglobin levels, hematocrit percentage, and erythrocyte index values (MCV, MCH, MCHC). It concluded that the feeding of Spirulina platensis for 35 days in ration can reduce total broiler erythrocytes and feeding S. platensis as a prebiotic given for 7 or 21 days of administration gives the same result as giving AGPs (Antibiotics Growth Promoters) seen from the broiler's red blood profile.